Effect of Entrepreneurial Marketing on SME Performance in Southern Province, Sri Lanka - Punchihewa, P.S.D.; Jayampathi, E.K. (International Journal of Small and Medium Enterprises and Business Sustainability, 2021)
Searching for new opportunities to increase firms’ performance is necessary when facing fierce competition. The entrepreneurial firms display more innovative, risk taking, and opportunity focused behavior than rival firms because of their entrepreneurial marketing behavior. Entrepreneurial Marketing is the marketing of small and medium enterprises (SMEs) growing through entrepreneurship. The main focus of this study was to identify the impact of entrepreneurial marketing on firms’ performance with moderating impact of gender. Southern province in Sri Lanka has been selected as the research site of this study. The researcher has selected the SMEs who were registered at the Chamber of Commerce and Industries of Matara, Galle and Hambanthota districts as the study population. Out of the total population, 114 SME entrepreneurs were selected for the sample using random sampling technique. Selfadministered questionnaire was used to collect primary data and secondary data sources were also used. Pearson correlation and regression analysis were applied to analyze the data. The study reveals, there is a positive impact of entrepreneurial marketing on firm entrepreneurial performance. Opportunity focus, risk taking, innovativeness, resource leveraging, customer intensity and value creation are the key factors which affect entrepreneurial firm performance whereas proactiveness has very little role as they are lack in forward-looking thoughts which can forecast future market needs accurately. The results depict that there is a significant positive relationship between gender and firm performance, with female entrepreneurs having a higher performance than their male counterparts. The study identified the necessity to place a high attention for satisfying their customer, which in return plays an important role for SMEs of doing business and marketing practices. Entrepreneurs should be concern on modern marketing strategies and techniques to boost their entrepreneurial capabilities and capacities to run their businesses with successful outcomes. Finally, the study provides practical implications for practitioners and theoretical implications for researchers as an array of progressive areas for future endeavors.